Understanding environment - Chhokar, Kiran Banga; Pandya, Mamata; Meena Raghunathan (New Delhi ; Thousand Oaks, Calif. : Sage Publications, 2004)
Designed as a basic text for foundation and undergraduate courses in Environmental Studies, this book introduces students to key scientific concepts related to environment and sustainable development. It provides a comprehensive understanding of environmental concerns and issues with special reference to the Indian context. The primary objective of the book is to create an awareness of the environment. It conceptualizes the environment as a multidimensional and complex living system and describes the interlinkages that make up this system. The presentation is supported by relevant examples
Includes bibliographical references and index.
Keywords: Environmental sciences -- Study and teaching (Higher) -- India; Environmental education -- Study and teaching (Higher) -- India; Sustainable development -- Study and teaching (Higher) -- India